REACTION OF RADIOMETRIC PARAMETERS TO ATMOSPHERIC POLLUTION : PART II -A COMPARATIVE STUDY BETWEEN PAIRS OF STATIONS - DESIKAN, V.; CHIVATE , V. R.; ABHYANKAR, V. V. (MAUSAM, 1994)
In part1,the effect ofatmosphe ric pollution overtime at a ai"-e n location \\'3$ discussed.The parricu late mat ter generated O"U a place is dispersed to surrounding areal> Thus II comp arative stud)'between pain of station s is worthwhil e. The effect of indust rial activi ty is clearly seen in the case of New Delhi when compared to Jodhpur. However, the changes are not h~ly sienificanl in the case cfihe already de veloped areas like Ahmedabad And Calcutta. Almost all statio ns show 8 decreasing trend in the net QUlgoina terrestrial radiant ent'rlf)'.